Cathodic Reduction of Nd(III) In-Situ Complexes with Some Organic Acids on DME - Lavale, S.C.; Sahu, G.P. (Asian Journal of Chemistry, 2016)
In this note, we report in-situ reduction of iminodiacetic acid (IDA), nitrilotriacetic acid (NTA) and diethylenetriamine pentaacetic acid (DTPA) complexes with neodymium(III) on mercury drop cathode. These form 1 : 1 complexes in each case with log β values 4.58, 5.01 and 5.39 respectively, which follows the order of IDA < NTA < DTPA. At pH = 2.6 ± 0.01, for mixed system-ligand displacement technique has been revealed, 1 : 1 : 1 mixed complex formation of [Nd-IDA-NTA] log β11 = 5.23 was computed. Under various experimental set-ups to search for pure and mixed complexation is in progress.